Analysis of 5G Capacity in Line-Of-Sight Condition of Urban Macro (UMa) Using 3.5 GHz Frequency - Yaser, Muhammad (Jurnal Teknik Elektro Indonesia, 2024)
This study is projected to be the initial design for the implementation of 5G technology, particularly in the Urban Macro (UMa) scenario, with a frequency of 3.5GHz and a bandwidth of 100 MHz. 3GPP (3rd Generation Partnership Project) TR 38.901 recommends performing performance analysis with line-of-sight (LOS) situations using the propagation model urban macro (uMa). In this study, 100 users are distributed at random distances to examine system capacity using the frequency reuse factors K = 1/3 and K = 1/7. According to the calculation results, this study demonstrates that system capacity is dependent on user distribution arrangement and the frequency reuse factor approach used. A high frequency reuse factor increases bandwidth efficiency and yields more optimum capacity. Furthermore, distributing users near the base station will boost capacity.